Inner limiting membrane bridges within Bruch’s membrane defects in pathological myopia - Panda-Jonas, Songhomitra; Jonas, Jost B.; Jonas, Rahul A. (Scientific reports, 2022)
The purpose of the study was to examine peculiarities of the inner limiting membrane (ILM) in axially elongated eyes. The histomorphometric study included human globes enucleated due to reasons such as painful secondary angle-closure glaucoma or malignant uveal melanomas. Using light microscopy, we searched for regions with ILM-specific features in association with a marked axial elongation. Out of 279 eyes (279 patients) (mean age: 61.8 ± 13.9 years; axial length: 25.5 ± 3.1 mm (range: 20.0-37.0 mm)), two eyes (axial length: 30 mm and 34 mm, respectively) showed one region and two regions, respectively, characterized by ILM presence and absence of all other retinal layers, retinal pigment epithelium, Bruch´s membrane (BM) and choroid. The length of these regions, called ILM-bridges, was 1.06 mm, 0.73 mm, and 0.62 mm, respectively. All ILM-bridges were spatially associated with a larger, underlying BM defect and with localized scleral thinning without a staphylomatous scleral configuration. The distance between the ILM-bridges and the optic disc ranged between 1.92 mm and 4.21 mm. In univariable analysis, ILM-bridge number increased with longer axial length (beta: 0.19; P = 0.002) and higher BM defect prevalence (beta: 0.21; P = 0.001), while in multivariable analysis, the ILM-bridges number remained to be significantly correlated only with a higher prevalence of BM defect (beta: 0.15; P = 0.048). ILM-bridges occur in eyes with pathologic myopia in spatial association with underlying, larger BM defects. They may be due to an axial elongation-associated local stretching and rupture of all other retinal layers, caused by the BM defect-related enlargement of the retinal undersurface. Future studies may explore whether these histologic observations support the notion of the ILM having a relatively high biomechanical strength against myopic stretching-associated forces.